2014
DOI: 10.1017/s0952523814000182
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity in relapsing–remitting multiple sclerosis assessed by sine-wave gratings and angular frequency stimuli

Abstract: Previous studies have shown that multiple sclerosis (MS) affects the visual system, mainly by reducing contrast sensitivity (CS), a function that can be assessed by measuring contrast sensitivity function (CSF). To this end, we measured both the CSF for sine-wave gratings and angular frequency stimuli with 20 participants aged between 21 and 44 years, of both genders, with normal or corrected to normal visual acuity. Of these 20 participants, there were 10 volunteers with clinically defined MS of the relapsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Our findings bear similarity to contrast sensitivity deficits recently reported for multiple sclerosis (MS) [22]. MS is an inflammatory, neurodegenerative autoimmune disease [30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings bear similarity to contrast sensitivity deficits recently reported for multiple sclerosis (MS) [22]. MS is an inflammatory, neurodegenerative autoimmune disease [30].…”
Section: Discussionsupporting
confidence: 91%
“…Optic neuritis is common [31] along with reports of loss of vision, colour vision disturbances, pain in the eyes, blurred vision, and visual fatigue [30,31]. A number of studies have examined contrast sensitivity in MS, and although the spatial frequency specificity varies between studies, there is agreement that poor contrast sensitivity is associated with the condition [20,21,22]. MS and ME share phenomenology and neuroimmune characteristics [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of low-contrast vision and CSV were sensitive to visual impairment, even in patients with VA of 20/20 or better (measured with a Snellen chart), and have been correlated with poorer performances in everyday tasks [8, 1720]. Our patients presented reduced CSV in low and midspatial frequencies and low-contrast VA compared with healthy controls, which is consistent to previous research involving classic visual function tests [11, 21, 22] and tests performed with other video processors [23, 24]. However, high spatial frequencies were not significantly affected in our patients, contrary to previous findings [11, 24].…”
Section: Discussionsupporting
confidence: 89%
“…Many studies demonstrated that deterioration in contrast sensitivity, visual field, and RNFL thickness may cause difficulty in a patient’s daily life. 18 23 So, in the present study, radiation dose–volume damage relation on anterior visual pathways was evaluated by visual field, contrast sensitivity, RNFL thickness, VEP latency, and VEP amplitude measurements besides VA.…”
Section: Discussionmentioning
confidence: 99%